Rapid design and deployment of intensive outpatient, group-based psychiatric care using telehealth during coronavirus disease 2019 (COVID-19) - Childs, Amber W (J Am Med Inform Assoc, 2020)
COVID-19 has demanded unprecedented actions in the delivery of outpatient psychiatric services, including the rapid shift of services from in-person to telehealth in response to public health physical distancing guidelines. One such shift was to convert group-level intensive outpatient psychiatric (IOP) interventions to telehealth. Historically, telehealth in psychiatric care has been studied in provider-patient interactions, but has not been as well studied for group telehealth service delivery. During the COVID-19 outbreak, providing group-based interventions was important in order to care for high-risk individuals who needed structured psychotherapy group support. However, the delivery of services via telehealth led to special challenges that were unable to be fully accommodated by the preexisting telehealth infrastructure. Rapid feasibility testing and adoption of technology was needed to support IOP services to minimize infectious spread while delivering group services to high-risk psychiatric patients. This article describes the processes and workflows for service delivery and early results of telehealth for IOP services in 2 adolescent treatment programs. In addition, the article highlights early observations around safety and quality and the role of telehealth policy and payment.